PELATIHAN PENULISAN KARYA ILMIAH UNTUK PESERTA DIDIK DI SMAN 1 TINAMBUNG KABUPATEN POLEWALI MANDAR - Fausan, Muhammad Mifta; Pujiastuti, Indah Panca; Sainab, Sainab (Batara Wisnu : Indonesian Journal of Community Services, 2024)
This community service program aims to enhance the research and scientific writing capabilities of students at SMA Negeri 1 Tinambung. The principal challenge identified at the partner school involves the students’ limited exposure to scientific writing that could strengthen their research abilities and competitive in national scientific competitions. Therefore, this community service program was designed to equip students with basic research skills. Additionally, students were provided with knowledge about scientific papers, including their definition, objectives, benefits, characteristics, types, structure, and examples of national student research olympiads. The program was conducted from April to June 2024. A total of 19 students participated in this program. The implementation stages included planning, training execution, and evaluation. Based on the evaluation results, it was found that students were able to develop research proposal frameworks comprising title, abstract, introduction, literature review, and research methodology. Questionnaire results regarding the program implementation quality also showed that participants gave positive assessments across various aspects of the training, with an average score of 4.86, indicating that the training was well-executed and effective.